Implementation of cleaner production strategies for offset lithography printing industry / Ramli Abd Rahman - Ramli, Abd Rahman (2017)
Malaysia is starting the journey towards greening its industries, especially the Small and Medium Industries (SMIs) where there are more than 600,000 of active one. There are many strategies that can be implemented to achieve green industry status. One of the strategies is Cleaner Production (CP) which was introduced in Malaysia in 2000 even though its implementation is still not widespread. In this study, Cleaner Production strategy will be used to demonstrate the feasibility of using the strategy in greening the printing industry. For this purpose, a printing premise with an annual production capacity of 300 tons was selected as a case study. Initially a CP audit was conducted systematically and options were generated using various components focusing on energy consumption, solid waste and scheduled waste generation. Subsequently, the options were evaluated in terms of carbon emission reduction, a major criteria in greening the industry. The results showed that the total carbon dioxide (CO2) emission generated at the premise was 244.6 tons per month, of which electricity consumption was the main contributor. More than 100 options were generated targeting on reducing CO2 emission through various means. Implementations of nine (9) major options are expected to reduce the CO2 emission of the premise as much as 190,718 tons per month which is a reduction of 78%. Of the nine (9) options proposed, there are four (4) options that can be implemented without any cost incurred. By implementing these options, 96.5 tons of CO2 emission or 0.321 tons of CO2 emission per ton of paper can be reduced monthly by the premise. These four options if implemented by 1000 active printing premises in Malaysia will result in CO2 reduction of 96,510 tons per month. By assuming, 15% of 600,000 SMEs in Malaysia are implementing these four options, about 8.7 million tons of CO2 can be reduced per month. The study proves that CP strategy can be used for greening the industry, which has been reflected in the study where proposed CP options are capable of reducing CO2 emission in the printing premise. The process of greening the industry, which adopts the CP strategy can be extended to other types of industries as well. This concludes that the greening of industry can be achieved by implementing CP in the premise of the industry especially the manufacturing premises.